KAJIAN PUSTAKA FAKTOR-FAKTOR YANG MEMPENGARUHI PERATAAN LABA SEBAGAI PRAKTIK MANAJEMEN LABA - Dhenta Agusti Widyantoro; Imroatul Lutfiana; Alfira Tiara Karisma; Aldalita Ajeng Rahmadani; Ardyan Firdausi Mustoffa (Jurnal Bina Akuntansi, 2023)
One of the valuation tools used to analyze financial statements is the profit earned by a company in order to be able to present good and appropriate company profits. The earnings management practice that companies tend to use is called "Income smoothing." Income smoothing is one way for entity management to increase or decrease profits by reducing fluctuations in profits from year to year. Income smoothing is often used to increase profits from a high-income year to a year that does not meet a company's profit standards. The population used in this article review is all SINTA accredited research results for the 2015–2021 period regarding components that affect income smoothing. data analysis method with descriptive and qualitative analysis approach. There are several components that influence the practice of equalizing profits, namely company size, profitability, cash holding, and company value. This research was conducted after collecting research results on income smoothing factors through literature studies.